2020
DOI: 10.1093/petrology/egaa029
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Compositional Evolution of Crustal Magmatic Systems from Coupled Petrological-Geodynamical Models

Abstract: The evolution of crustal magmatic systems is incompletely understood, as most studies are limited either by their temporal or spatial resolution. Exposed plutonic rocks represent the final stage of a long-term evolution punctuated by several magmatic events with different chemistry and generated under different mechanical conditions. Although the final state can be easily described, the nature of each magmatic pulse is more difficult to retrieve. This study presents a new method to investigate the compositiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…Petrological studies and thermodynamic models have long indicated that crustal magmatic reservoirs (i.e., magma chambers) contain an abundance of crystal mush, where “mush” refers to a system with melt contained in a framework of crystals (Cashman et al., 2017; Marsh, 1989, 2013; Pritchard et al., 2018; Wieser et al., 2020). Crystals have thermal and geochemical importance, as they can alter the chemistry and thermal state of magma, and provide constrains on the thermal state and timescales of magma storage, ascent, and eruption (Antonelli et al., 2019; Bachmann & Huber, 2016; Cooper, 2019; Costa et al., 2020; Rummel et al., 2020; Singer et al., 2018; Sparks & Cashman, 2017). In recent decades, many research efforts have been devoted to understanding how crystal mush evolves and interacts with magma, using quantitative models and principles in thermodynamics, geochemistry, and geophysics.…”
Section: Background: Magma Chamber Model With Poroelastic/viscoelastic Mushmentioning
confidence: 99%
“…Petrological studies and thermodynamic models have long indicated that crustal magmatic reservoirs (i.e., magma chambers) contain an abundance of crystal mush, where “mush” refers to a system with melt contained in a framework of crystals (Cashman et al., 2017; Marsh, 1989, 2013; Pritchard et al., 2018; Wieser et al., 2020). Crystals have thermal and geochemical importance, as they can alter the chemistry and thermal state of magma, and provide constrains on the thermal state and timescales of magma storage, ascent, and eruption (Antonelli et al., 2019; Bachmann & Huber, 2016; Cooper, 2019; Costa et al., 2020; Rummel et al., 2020; Singer et al., 2018; Sparks & Cashman, 2017). In recent decades, many research efforts have been devoted to understanding how crystal mush evolves and interacts with magma, using quantitative models and principles in thermodynamics, geochemistry, and geophysics.…”
Section: Background: Magma Chamber Model With Poroelastic/viscoelastic Mushmentioning
confidence: 99%
“…Caricchi et al (2016) explored the magma flux range of 10 −4 -10 −1 km 3 /a, Gelman et al (2013) studied magma injection into a cylindrical domain with the radius of 10 km and magma fluxes of 0.005-0.03 km 3 /a. Other authors (Karakas et al, 2017;Rummel et al, 2020;Tierney et al, 2016) suggest magma fluxes of 0.1-6 ×10 −3 km 3 /a. A global compilation of 170 time-averaged volumetric volcanic output rates was collected in the study White et al (2006).…”
Section: Resultsmentioning
confidence: 95%
“…The intruding basalts will thus in turn play an important role in increasing the magma production rate. Magma advection via diking are difficult phenomena to implement even in advanced 2‐D or 3‐D models because the processes depends on many complex, dynamic processes, and parameters such as rock rheology, melt transport, phase transition, and dike formation mechanisms (e.g., Cao et al., 2016a; Liang & Parmentier, 2010; Rummel et al., 2020). While others have quantitatively assessed the process of advective magma transport and the thermal impact of mantle melt on the lithosphere using sophisticated, two‐phase flow dynamics (Keller et al., 2013; Rees Jones et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(2) We assume all melts are added to the arc crust as soon as they are generated. There is no lag time associated with melt transport, and the physical processes of magma ascent and emplacement (e.g., Cao et al., 2016a; Rummel et al., 2020) are not considered. (3) Magma advection as dikes or diapirs are not included.…”
Section: Methodsmentioning
confidence: 99%